Age of peak swim speed and sex difference in performance in medley and freestyle swimming - a comparison between 200 m and 400 m in Swiss elite swimmers - Vaso, M.; Knechtle, B.; Rüst, C. A.; Rosemann, T.; Lepers, R. (Journal of Human Sport & Exercise, 2013)
The aims of the present study were to examine (i) the age of peak swim speed and (ii) the sex difference in peak swim times in 200m and 400m medley versus freestyle. Swim times and ages of 5,524 swimmers (2,785 males and 2,739 females) from the Swiss high score list from 2006 to 2010 were analyzed using one-way analysis of variance (ANOVA). The age of peak swim speed was younger for females (~20-21 years) compared to males (~22-25 years) for both distances and both swimming styles. The sex differences in peak swim times for age group 10-39 years were 9.7% (SD=3.4) and 7.1% (SD=5.1) for 200m and 400m individual medley, and 10.1% (SD=5.0) and 6.1% (SD=4.0) for 200m and 400m freestyle, respectively. The sex differences were neither different between the two distances nor between the two disciplines (p > .05). There were no differences within each sex (i.e. females to females, and males to males) in the age of reaching peak swim speed in 200m and 400m individual medley and freestyle. However, females reached the peak swim speed at a younger age than males. The sex differences in peak swim times were similar for 200m than for 400m for both swim styles. To summarize, the present findings suggest no difference in the age of peak swim times in 200m and 400m individual medley and freestyle. However, females reached peak swim times earlier than males, which might be dependent on a different development of the genders in puberty and the related physiological and anthropometric factors. Sex differences in peak swim times were similar for 200m than for 400m for both swim styles.